Race, Internet usage, and E-commerce - Hiroshi Ono; Madeline Zavodny (Federal Reserve Bank of Atlanta, 2002)
The authors examine racial and ethnic differences in computer ownership and Internet usage using data from a survey conducted by the Nomura Research Institute in 2000. They focus on on-line shopping because few studies have examined racial and ethnic differences in e-commerce. The results indicate that blacks and Hispanics are less likely to own or use a computer than are non-Hispanic whites but are not less likely to shop on-line. Indeed, blacks appear to shop on-line more frequently and to spend more than non-Hispanic whites do.
Keywords: 330; Internet; Electronic commerce; Consumer behavior